PERAN PANCASILA DALAM KEMELUT KEHIDUPAN BERBANGSA DAN BERNEGARA - Lala Karmila Sari; Dinie Anggraeni Dewi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE ROLE OF PANCASILA IN THE CRISIS OF NATIONAL AND STATE LIFEThe inculcation of Pancasila values that should have happened but instead became a material without being implemented. That's what happens in our lives now. Lots of turmoil that has occurred so far have not found a bright spot for improvement of living systems. This writing aims to provide a picture of the chaos that occurs in the life of the nation and state that occurs in our environment. The various problems that occur are of course contrary to the values that exist in Pancasila as a pillar of nationality. The research method used is literature study, where researchers dig up information from various books, scientific papers, the internet, and others, for the research material used. The results of the research from the author's literature show that there are still many citizens who do not apply the values of Pancasila in their daily lives. This emphasizes that it is very important that Pancasila education is taught from elementary to tertiary level.